Ramadhan Themes in Islamic Education Using Upin and Ipin Media - Ariyanto, Fiqi; Fahyuni, Eni Fariyatul (Indonesian Journal of Islamic Studies, 2024)
General Background: Audio-visual media are crucial in education, enhancing students' understanding and retention. Specific Background: In Islamic Religious Education (IRE), particularly during the Ramadhan fasting theme, effective use of audio-visual media can engage students actively. However, there is a gap in knowledge regarding their application in elementary schools. Aims: This study examines how teachers at Jagul State Elementary School utilize audio-visual media, specifically the animated series "Upin and Ipin," in IRE. Results: Through descriptive qualitative research, findings indicate that the implementation of audio-visual media significantly improves students' learning outcomes, as evidenced by increased motivation and comprehension. Novelty: This study highlights the effective integration of engaging audio-visual materials in religious education. Implications: The research suggests that incorporating audio-visual media in IRE fosters a more dynamic learning environment, encouraging educators to adopt innovative teaching methods to enrich student experiences. Highlights: Enhanced Engagement: Audio-visual materials like "Upin and Ipin" actively involve students in the learning process. Improved Comprehension: The use of audio-visual media significantly boosts students' understanding of Islamic concepts. Dynamic Learning Environment: Incorporating innovative teaching methods fosters a more effective and enjoyable educational experience. Keywords: Audio-Visual Media, Islamic Education, Ramadhan, Student Engagement, Learning Outcomes